Capital Structure Effect On Net Working Capital And Asset Management To Profitability - Adli Saputra; Alfian Zata Thirafi; Milah Fadhilah Kusuma Fasihu; Farah Margaretha; Henny Setyo Lestari (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2024)
Competition in the industrial sector is increasing as more companies are established. This is a sign of the development of the Indonesian economy. Companies face various competitions, compete for their performance, and aim to achieve goals and growth. The profitability of a company can be influenced by many factors such as asset management, capital structure, and company size. Companies that know how to manage assets well can achieve maximum profit. In carrying out its operations, the company's assets are used to generate profits The capital structure can affect profitability because the capital structure decision is one of the very important financial strategies that the Company must face Therefore, in addition to affecting the profitability of the company, financial problems caused by the capital structure have a significant impact on macroeconomic outcomes.